2016
DOI: 10.14740/jcs306e
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Polydioxanone and Nylon for Abdominal Wall Closure With Interrupted Figure of Eight in Peritonitis Cases

Abstract: Background: In emergency and elective settings, some surgeons prefer continuous or interrupted closure of abdominal fascia, because in a continuous suturing, cutting out of even a single bite of tissue leads to opening of the entire wound and high risk of burst abdomen, whereas in interrupted method, they found much lower risk of burst abdomen. The aim is to assess the complication rate with the same closure technique between two different sutures. The best suture is one that maintains tensile strength through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…7,8,[12][13][14][15] It is quite evident that suture sinus formation frequently occurs with non-absorbable sutures like nylon/ prolene because of its long memory, stiff nature and tissue reactivity. The present study observed that suture sinus formation is more prevalent with prolene (5.9%) and this was consistent with findings of the studies conducted by Singal et al, Bloeman et al and Gaikwad et al 7,10,11 Present study demonstrated the incisional hernia rate as 3.1% in PDS group and 14.7% in prolene group (p>0.05). This is not in consonance to study done by Bloeman et al which showed the rate of incisional hernia to be more…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7,8,[12][13][14][15] It is quite evident that suture sinus formation frequently occurs with non-absorbable sutures like nylon/ prolene because of its long memory, stiff nature and tissue reactivity. The present study observed that suture sinus formation is more prevalent with prolene (5.9%) and this was consistent with findings of the studies conducted by Singal et al, Bloeman et al and Gaikwad et al 7,10,11 Present study demonstrated the incisional hernia rate as 3.1% in PDS group and 14.7% in prolene group (p>0.05). This is not in consonance to study done by Bloeman et al which showed the rate of incisional hernia to be more…”
Section: Discussionsupporting
confidence: 92%
“…Studies conducted by Israelsson et al and Van't et al also found similar results. 8,9 The wound discharge rate was 28.1% in PDS group while 26.5% in the prolene group (p>0.05) This was consistent with the results of the studies conducted by Singal et al, Bloeman et al and Gaikwad et al 7,10,11 More number of patients suffered from abdominal wound dehiscence in the PDS group but this was found to be statistically insignificant. But Gaikwad et al reported contrary findings with the PDS group, which showed a very high incidence of wound dehiscence, which has not been reported in any previously performed study.…”
Section: Discussionsupporting
confidence: 88%
“…As with any new medical device, the biological evaluation of the device and material constituents must be carefully assessed. Polydioxanone—the polymer used for filament manufacture, was selected on the basis of history of safe clinical use [17, 52, 53]. Addition of pyridine into the polymer solution must be carefully considered within the framework of the wider biological evaluation, which is guided by ‘ISO 10993 Biological evaluation of medical devices’ and a risk based approach must be adopted to the use of any additional raw materials (including solvents and controlled impurities).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of postoperative surgical site infection remains high at 3-20%, making it the most important early postoperative complication of midline laparotomy (incisional hernia is reported at 15% after open abdominal surgery, wound dehiscence at 0.5-3.4% and wound sinus at between 0-3.5%). 3,27,41,42 Reports that fewer colony forming units of bacteria are required to produce surgical site infection in the presence of suture material date back to 1957. 43 It is as a result of this understanding that triclosancoated sutures were developed, with the expectation that asepsis may reduce the number of colony forming units able to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one studies (summarised in Table 1) were identified that were appropriate in their question and SURGERY IN GENERAL Table 1 Author quality. These included studies investigating polyglactin, 1,4,[6][7][8][9][10][11][12][13][14] polydioxanone (PDS), 5,[15][16][17][18][19][20][21][22][23][24][25][26][27] polypropylene, 28,29 nylon, [30][31][32] polyglycolic acid (PGA), 33 polyglyconate, triclosan-coated polyglactin, triclosan-coated polydioxanone, Ethibond®, steel, poly(L-lactide-co-glycolide) (PLG) and Polysorb®.…”
Section: Introductionmentioning
confidence: 99%